2020
DOI: 10.1002/jso.26214
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence patterns in patients with Stage II melanoma: The evolving role of routine imaging for surveillance

Abstract: Background and Objectives: The relatively recent availability of effective systemic therapies for metastatic melanoma necessitates reconsideration of current surveillance patterns. Evidence supporting surveillance guidelines for resected Stage II melanoma is lacking. Prior reports note routine imaging detects only 21% of recurrent disease. This study aims to define recurrence patterns for Stage II melanoma to inform future surveillance guidelines. Methods: This is a retrospective study of patients with Stage I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Thus, it is likely that the Nx group did not truly have undetected higher-stage primary Five-year survival rates in our cohort paralleled those of prior studies, but recurrence rates were lower than expected. [2][3][4][5][6][7] The present study focuses primarily on routine 18 F-FDG PET/CT for Stages IIB, IIC, and IIIA, while prior studies investigating the role of PET in melanoma surveillance have reported different ranges of A strength of this study is the emphasis on the predictive values of routine 18 F-FDG PET/CT as a marker of the clinician's confidence in the effectiveness to detect asymptomatic recurrence or reassure asymptomatic patients. A high NPV in this cohort provides patient reassurance after negative results, whereas a relatively high FP rate in this particular patient population clouds the clinical decision-making process after positive results.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, it is likely that the Nx group did not truly have undetected higher-stage primary Five-year survival rates in our cohort paralleled those of prior studies, but recurrence rates were lower than expected. [2][3][4][5][6][7] The present study focuses primarily on routine 18 F-FDG PET/CT for Stages IIB, IIC, and IIIA, while prior studies investigating the role of PET in melanoma surveillance have reported different ranges of A strength of this study is the emphasis on the predictive values of routine 18 F-FDG PET/CT as a marker of the clinician's confidence in the effectiveness to detect asymptomatic recurrence or reassure asymptomatic patients. A high NPV in this cohort provides patient reassurance after negative results, whereas a relatively high FP rate in this particular patient population clouds the clinical decision-making process after positive results.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found benefits for CT surveillance in Stage II melanoma, but prospective comparative studies between 18 F-FDG PET/CT and CT are needed to address the question of which modality is superior for this patient population. 3 Increased melanoma survivorship due to increasing incidence and a stable mortality rate has led to a greater need for surveillance. 29 Multidisciplinary care by the dermatologist, surgical oncologist, and medical oncologist is essential for patients with high-risk Stages II and III melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations